2019
DOI: 10.1167/iovs.19-27531
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Axial Length and Diabetic Retinopathy: The Kailuan Eye Study

Abstract: Citation: Wang Q, Wang YX, Wu SL, et al. Ocular axial length and diabetic retinopathy: the Kailuan Eye Study. Invest Ophthalmol Vis Sci. 2019;60:3689-3695. https://doi.org/ 10.1167/iovs.19-27531 PURPOSE.To examine the role of ocular axial length as an ocular parameter for the prevalence and severity of diabetic retinopathy (DR). METHODS.The cross-sectional Kailuan Diabetic Retinopathy Study included patients with diabetes who participated in the community-based longitudinal Kailuan Study and who had undergone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Longer AL was associated with lower risk for both DR and VTDR, which was consistent with previous studies. Several population‐based studies suggested that AL played a different role in DR occurrence and development in different ethnicities, although some contradictory results existed in literature (He et al 2017; Bikbov et al 2019; Wang et al 2019). It was reported that AL was not related to DR based on Indian population(Ganesan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer AL was associated with lower risk for both DR and VTDR, which was consistent with previous studies. Several population‐based studies suggested that AL played a different role in DR occurrence and development in different ethnicities, although some contradictory results existed in literature (He et al 2017; Bikbov et al 2019; Wang et al 2019). It was reported that AL was not related to DR based on Indian population(Ganesan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the ocular structure or the refracting media, or both, could be a protective factor of DR is still under debate. Several studies have evaluated the association of axial length (AL), myopia and refracting media with DR (Chao et al 2016; He et al 2017; Bikbov et al 2019; Man et al 2019; Wang et al 2019). However, the investigators have not yet reached a consensus on the implications of these results.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was a prospective observational cohort of 34 patients who were recruited from the Beijing Tongren Eye Centre with a diagnosis of RP from January 2019 to October 2019. For retinal evaluation, 32 normal control individuals were recruited from the Kailuan Eye Study as the control group, who were age- and gender-matched with the RP patients [ 10 ]. For choroidal evaluation, 17 normal control eyes from patients were recruited from the outpatient department in Beijing Tongren Eye Centre who underwent VG-200 OCTA examination and other ophthalmic examinations.…”
Section: Methodsmentioning
confidence: 99%
“…The Kailuan Diabetic Retinopathy Study indicated that subfoveal CT decreased with AL elongation among 1,154 diabetic participants. 5 However, both these studies did not analyze the relationship between AL and CT in other macular subgrids. The reverse relationship between AL and foveal CT was also confirmed in high myopic eyes, 29 young health adults, 30 those with angle closure, 31 and population-based studies.…”
Section: Discussionmentioning
confidence: 99%